(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2023)
Introduction: Parkinson’s is a chronic and progressive neurodegenerative disorder. Worldwide, disability from Parkinson’s is increasing faster than that from any other neurological disorder. Parkinson’s patients face numerous barriers to accessing face-toface rehabilitation services. For this reason, in recent years telerehabilitation has been proposed as a possible solution to this problem. The main objective of this work is to carry out a review of the literature on the applications of telerehabilitation in patients with Parkinson’s. Method: A review was carried out following the PRISMA regulations. The PubMed, Cinahl, PsycINFO, SPORTDiscus, Academic Search Complete, Lilacs, IBECS, CENTRAL, SciELO, and WOS databases were consulted. The Cochrane tool was used to assess the risk of bias and the quality of the evidence was assessed GRADE. Results: Telerehabilitation is effective in patients with Parkinson’s. The total sample was 256 patients. The number of telerehabilitation sessions ranged from 15 to 28 sessions, each lasting between 40 and 90 minutes. The total treatment lasted between 4 and 8 weeks and the frequency was between 1 and 3 times per week. Conclusions: Telerehabilitation is an effective alternative to clinical treatment to reduce postural instability, improve postural control, maintain speech, and improve strength. This therapy offers advantages over conventional face-to-face rehabilitation in clinic for patients with mobility difficulties.